HUBUNGAN ANTARA LINGKUNGAN KERJA DAN KERJASAMA TIM DENGAN KEPUASAN KERJA - Marliza Oktapiani (Jurnal Manajemen Pendidikan, 2011)
The Objectivity of study is to examine the work Environment and Teamwork in improving to lecture's job satisfaction teacher's at Raudhatul Athfal of Duren Sawit region east Jakarta. In this study, the method applied is descriptive quantitative method. Analysis unit refers lecture's job satisfaction at Raudhatul Athfal of Duren Sawit region east Jakarta . Instrument applied in collecting of data it is questioner.This study covers: (1) is the work Environment lecture's job satisfaction teacher's at Raudhatul Athfal (2). Is the Teamwork in improving to lecture's job satisfaction teacher's at Raudhatul Athfal and (3) Are the work Environment and Teamwork in collective improving to lecture's job satisfaction teacher's at Raudhatul Athfal. The result of this study indication thatcorrelation between work Environment and job satisfaction are very significant, correlation between Teamwork and job satisfaction is significant and finally correlation between work Environment and Teamwork in collective to lecture's job satisfaction have regression line equation and it is able to test in corrective. Therefore, this correalation should be maintained and developed to achieve better than relations so as to provide benefits for teachers and Raudhatul Athfal, as more and better relationship, so higher the job satisfaction.